The challenge of measuring poverty and inequality: a comparative analysis of the main indicators - Juan Ignacio Martiń-Legendre (European Journal of Government and Economics (EJGE), 2018)
This paper presents a review of the main available indicators to measure poverty and income inequality, examining their properties and suitability for different types of economic analyses, and providing real-world data to illustrate how they work. Although some of these metrics -such as the Gini coefficient- are most frequently used for this purpose, it is crucially important for researchers and policy-makers to take into account alternative methods that can offer complementary information in order to better understand these issues at all levels.
Keywords: 330; income inequality; indicators; inequality metrics; poverty metrics